Law and order in a weak state : crime and politics in Papua New Guinea - Dinnen, Sinclair (Center for Pacific Islands Studies, School of Hawaiian, Asian, and Pacific Studies, University of Hawai'i Press, 2001)
Twenty-five years after independence, Papua New Guinea is beset by social, economic, and political problems: poverty and inequality, a young and expanding population, a stagnant economy, corruption, and rising crime. This book examines these problems of order in light of Papua New Guinea's remarkable social diversity and the impact of rapid and pervasive processes of change. Three original and strategic case studies involving urban gangs, mining security, and election violence form the core of the work. Each case study looks at particular forms of conflict, and the responses these engender, across different socioeconomic contexts and geographic locations. Empirical data are analysed through a common framework that employs material, cultural, and institutional perspectives, allowing readers to view the three cases through different theoretical prisms, identify link-ages between them, and, in the process, build a larger picture of the post-colonial social order.
Keywords: Crime prevention -- Papua New Guinea.; Crime -- Papua New Guinea.; Surety of the peace -- Papua New Guinea.; Papua New Guinea -- Politics and government -- 1975-; Engagement de ne pas troubler l'ordre public -- Papouasie-Nouvelle-Guinée.; Papouasie-Nouvelle-Guinée -- Politique et gouvernement -- 1975-; SOCIAL SCIENCE -- Criminology.; Crime; Crime prevention; Politics and government; Surety of the peace; Papua New Guinea; Openbare orde.; Sociale orde.; Criminaliteit.; Ordehandhaving.; Papua Nieuw-Guinea.; Since 1975